Implementation and experimentation of network coding in DVB‐S2/RCS2 systems. (31st August 2017) - Erl, Stefan; de Cola, Tomaso
Summary: Applicability of network coding (NC) to satellite networks and related advantages has been long addressed and thoroughly analyzed by the scientific community in the last years, through theoretical approaches and simulations campaigns. Despite the great effort devoted to such analysis, few insights have been actually given to the NC implementation in real satellite systems and to the related validation. In particular, no recommendations on how to implement exemplary NC solutions in the widespread DVB‐S2/RCS2 system architecture have been given. In the attempt to bridge this gap, the present paper extends the DVB‐S2/RCS2 architecture so as to implement NC functions, operating between network and datalink layers. The study is corroborated by the implementation of the proposed protocol stack in a testbed closely reproducing a real system architecture. Finally, performance analysis results demonstrate the effectiveness of the proposed integrated architecture. Abstract : This study proposes the design of network coding for DVB‐S2/RCS2 satellite system, taking into account the characteristics of the full protocol architecture. The design has been implemented in a realistic testbed closing reproducing the main functionalities of a satellite system. The conducted emulation campaigns have shown the benefits of the proposed network coding design concept again regular satellite communication implementations.